(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Phraseological units are fixed expressions that carry cultural and linguistic significance, often reflecting the history, traditions, and worldview of a nation. This paper presents a comparative analysis of phraseological units in Uzbek and English, focusing on their structural, semantic, and cultural aspects. The study identifies similarities and differences in their formation, meaning, and usage, highlighting how cultural context influences idiomatic expressions. The research is based on examples from both languages, demonstrating how phraseological units function in communication and what challenges they may pose in translation.